Molecular recognition of the beta‐glucans laminarin and pustulan by a SusD‐like glycan‐binding protein of a marine Bacteroidetes. (28th October 2018) - Mystkowska, Agata Anna; Robb, Craig; Vidal‐Melgosa, Silvia; Vanni, Chiara; Fernandez‐Guerra, Antonio; Höhne, Matthias; Hehemann, Jan‐Hendrik
Abstract : Marine bacteria catabolize carbohydrate polymers of algae, which synthesize these structurally diverse molecules in ocean surface waters. Although algal glycans are an abundant carbon and energy source in the ocean, the molecular details that enable specific recognition between algal glycans and bacterial degraders remain largely unknown. Here we characterized a surface protein, GMSusD from the planktonic Bacteroidetes‐Gramella sp. MAR_2010_102 that thrives during algal blooms. Our biochemical and structural analyses show that GMSusD binds glucose polysaccharides such as branched laminarin and linear pustulan. The 1.8 Å crystal structure of GMSusD indicates that three tryptophan residues form the putative glycan‐binding site. Mutagenesis studies confirmed that these residues are crucial for laminarin recognition. We queried metagenomes of global surface water datasets for the occurrence of SusD‐like proteins and found sequences with the three structurally conserved residues in different locations in the ocean. The molecular selectivity of GMSusD underscores that specific interactions are required for laminarin recognition. In conclusion, our findings provide insight into the molecular details of β‐glucan binding by GMSusD and our bioinformatic analysis reveals that this molecular interaction may contribute to glucan cycling in the surface ocean. Abstract : Marine bacteria catabolize carbohydrates, which are synthesized by algae in ocean surface waters. Although algal glycans are an abundant carbon and energy source for marine microbes, the molecular details that enable bacteria for specific polysaccharides recognition remain largely unknown. We characterized surface glycan‐binding protein from the planktonic Bacteroidetes ‐ Gramella that thrives during algal bloom in Helgoland by consuming algal polysaccharides.